2006
DOI: 10.1128/aem.02780-05
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Heteropolysaccharide-Producing Lactic Acid Bacterium Strains and Their Biopolymers

Abstract: Thirty-one lactic acid bacterial strains from different species were evaluated for exopolysaccharide (EPS) production in milk. Thermophilic strains produced more EPS than mesophilic ones, but EPS yields were generally low. Ropiness or capsular polysaccharide formation was strain dependent. Six strains produced high-molecular-mass EPS. Polymers were classified into nine groups on the basis of their monomer composition. EPS from Enterococcus strains were isolated and characterized.Certain lactic acid bacteria (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
109
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(122 citation statements)
references
References 36 publications
11
109
0
2
Order By: Relevance
“…bulgaricus NCDC 285 were glucose: rhamnose : galactose in a proportion of 1 : 13 : 1.5 and rhamnose : galactose in a proportion of 1:6.8 respectively ( Table 1). The monosaccharides most frequently occurring in the various LAB strains are glucose (Cerning 1995), rhamnose (Mozzi et al 2006;Nakajima et al 1990) and galactose (De Vuyst et al 2003;Doleyres et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…bulgaricus NCDC 285 were glucose: rhamnose : galactose in a proportion of 1 : 13 : 1.5 and rhamnose : galactose in a proportion of 1:6.8 respectively ( Table 1). The monosaccharides most frequently occurring in the various LAB strains are glucose (Cerning 1995), rhamnose (Mozzi et al 2006;Nakajima et al 1990) and galactose (De Vuyst et al 2003;Doleyres et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Kefiranofaciens, isolated from a fermented food product Kefir in North Caucasus, were able to produce enormous amount of hetero-exopolysaccharides (De Vos et al, 2009;Harutoshi, 2013). A number of microbial species such as Streptococcus thermophilus, Lactococcus lactis, L. delbrueckii, and Lactobacillus helveticus have been well recognized with an ability to produce heteroexopolysaccharides (Mozzi et al, 2006) In addition, lactic acid bacteria of homo-fermentative nature are well known for their ability to produce hetero-EPS, whereas, a hetero-fermentative strain L. fermentum has been found to produce exopolysaccharide with confirmed chemical nature determination (Leo et al, 2007). Although previously presence of inadequate production of hetero-exopolysaccharides has been confirmed in L. brevis and L. buchneri in the growth medium containing glucose or sucrose as carbon sources, no results were reported on the origin (Figueroa et al, 1995 50-350, 80-600, 60-150, 50-60 and about 140 mg/liter of hetero-exopolysaccharide (Tallon et al, 2003;Tsuda and Miyamoto, 2010;Harutoshi, 2013).…”
Section: Hetero-exopolysaccharidementioning
confidence: 99%
“…subsp. bulgaricus, L. helveticus, L. paracasei, L. pentosus, L. plantarum, L., rhamnosus, L. reuteri, L. casei, Leuconostoc mesenteroides and Streptococcus thermophilus although it is a strain-dependent property (Mozzi et. al., 2006;Ruas-Madiedo et.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…(1994) reported anti-ulcer effects of the cell wall polysaccharide of bifidobacteria, lactobacilli and streptococci strains, which were attributed to the high rhamnose content of the polymers (> 60%). Rodríguez et al (2009Rodríguez et al ( , 2010 reported the first evidences on the beneficial effects of both the EPS-producing LAB strains and the biopolymer on gastritis experimental animal models using acetyl salicylic acid ( The strains CRL 1190 and CRL 87 also produced capsular polysaccharide in addition to the slime EPS in milk and was able to form ropy milk cultures similar to CRL 638, while the strain CRL 804 was negative for both the capsular and ropy phenotypes (Mozzi et. al., 2006).…”
Section: Wwwintechopencommentioning
confidence: 99%